New deep Cheilostomata (Bryozoa) species from the Southwestern Atlantic: shedding light in the dark - Figuerola, Blanca; Gordon, Dennis P.; Cristobo, Javier (Zootaxa, 2018)
The present paper reports on 22 bryozoan species collected from 25 localities on the Southwestern Atlantic continental shelf and slope by the Instituto Español de Oceanografía vessel RV Miguel Oliver (2008–2010). Two new genera, Amynaskolia n. gen. and Biconcavus n. gen., and twenty new cheilostome species are described: Amastigia zigzag n. sp., Membranicellaria balanyai n. sp., Figularia dimorpha n. sp., Biconcavus batmani n. sp., Smittina acicularis n. sp., Smittoidea granulosa n. sp., Amynaskolia foramina n. sp., Mawatarius avilae n. sp., Mucropetraliella reticulata n. sp., Ipsibuffonella umbonata n. sp., Microporella gappai n. sp., Fenestrulina curviscutum n. sp., Fenestrulina multiflorum n. sp., Malakosaria cecilioi n. sp., Osthimosia incisa n. sp., Spigaleos simplex n. sp., Reteporella kuklinskii n. sp., Reteporella maryae n. sp., Reteporella taylori n. sp., Orthoporidra nova n. sp.. New taxonomic remarks are also included for two little-known species: Melicerita atlantica Busk, 1884 and Arachnopusia tubula Hayward & Thorpe, 1988. Membranicellaria balanyai n. sp., Mawatarius avilae n. sp. and Ipsibuffonella umbonata n. sp. represent the third described species of their genera, whereas Spigaleos simplex n. sp., Malakosaria cecilioi n. sp. and Orthoporidra nova n. sp. are the fourth, fifth and sixth described species of their genera respectively. Spigaleos (Celleporidae) and Arachnopusia tubula (Arachnopusiidae), previously reported only from Antarctica, Ipsibuffonella (Buffonellodidae), reported from tropical and subtropical regions, and Mucropetraliella (Petraliidae) all represent first records for the Patagonian region, expanding their geographic distributions northwards and southwards, respectively. These results highlight the importance of sampling the slope and deep waters of South American and Antarctic margins and basins, filling significant gaps in the knowledge of the biodiversity and biogeographic ranges of certain taxa in these unique and varied ecosystems.